2020
DOI: 10.1021/acs.est.0c04941
|View full text |Cite
|
Sign up to set email alerts
|

Source–Receptor Relationship Revealed by the Halted Traffic and Aggravated Haze in Beijing during the COVID-19 Lockdown

Abstract: The COVID-19 outbreak greatly limited human activities and reduced primary emissions particularly from urban on-road vehicles but coincided with Beijing experiencing “pandemic haze,” raising the public concerns about the effectiveness of imposed traffic policies to improve the air quality. This paper explores the relationship between local vehicle emissions and the winter haze in Beijing before and during the COVID-19 lockdown based on an integrated analysis framework, which combines a real-time on-road emissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
64
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(74 citation statements)
references
References 62 publications
6
64
4
Order By: Relevance
“…The decreased traffic volume caused reduced NO emissions and likely led to a decline in local titration of O 3 (Sicard et al., 2020), contributing to a sharp increase in O 3 during the CSF holiday. This result is also in phase with existing literature that the decreased NO x emission over east China due to the lockdown led to a significant increase in surface O 3 and other atmospheric oxidants (HO 2 , NO 3 , and OH radical) through air quality modeling and measurements (Huang et al., 2020; Lv et al., 2020; Zhang et al., 2021).…”
Section: Resultssupporting
confidence: 89%
“…The decreased traffic volume caused reduced NO emissions and likely led to a decline in local titration of O 3 (Sicard et al., 2020), contributing to a sharp increase in O 3 during the CSF holiday. This result is also in phase with existing literature that the decreased NO x emission over east China due to the lockdown led to a significant increase in surface O 3 and other atmospheric oxidants (HO 2 , NO 3 , and OH radical) through air quality modeling and measurements (Huang et al., 2020; Lv et al., 2020; Zhang et al., 2021).…”
Section: Resultssupporting
confidence: 89%
“…For example, Liu et al estimated that global CO 2 emissions (1,551 metric tons) sharply decreased by 9% in the first half of 2020 compared with those in the same period of 2019 ( Liu et al, 2020 ). Lv et al found that the increase in secondary aerosols in China offset the benefit of the reduction in NOx and VOC emissions on air quality ( Lv et al, 2020 ). Other studies explored the health benefits of the improvement in air quality during the COVID-19 pandemic ( Alsayedahmed, 2020 ; Anderson et al, 2020 ; Markandeya et al, 2020 ; Giani et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…At the start of the COVID-19 pandemic, nationwide restrictive measures, such as stay-at-home recommendations, travel bans, cessation of public transportation, and the closing of shopping centers and entertainment venues, provided a unique opportunity to explore the dynamics and sources of PM 2.5 contamination. This was done by comparing changes in PM 2.5 concentrations and composition during different periods of the COVID-19 pandemic ( Liu et al, 2020 ; Lv et al, 2020 ; Tanzer-Gruener et al, 2020 ). The degree of local PM 2.5 contamination is determined by meteorological conditions, long‐range transportation and atmospheric chemistry, as well as local emissions, with these factors exerting synergistic effects on PM 2.5 pollution ( An et al, 2019 ; Chen et al, 2020b ; Wang et al, 2015 ; Zhao et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%